Gender diversity in the deans of brazilian universities: career temporal evolution, production of knowledge and of human resources - Nodari, Carolina; Oliveira, Claudio Celso Soares de; Barbosa, Marcia C. (Revista Brasileira de Pós-Graduação, 2024)
Women are underrepresented in positions of power and leadership in higher education and the challenges faced by women in order to reach these senior positions in academia are complex and have received considerable attention in recent years. In this work, we quantify gender diversity in Brazilian academia using three types of indicators: production of knowledge, temporal evolution in the career, and training of human resources to study in detail the profile of the Deans of Research and Graduate Studies in 215 Higher Education Institutions in the year of 2019. Our analysis shows that around only 36% of positions were occupied by women, a percentage that is not consistent with the number of women professors in Brazilian higher education. Using the National Council for Scientific and Technological Development Lattes’ Platform databank, we show that men and women in dean positions publish roughly the same number of paper/scientific articles per year and present almost the same time elapsed in the career path, while women produce more human resources. The fact that women occupy only 1/3 of the positions of dean of research and graduation reveals that for women to reach the top, it is necessary that they adapt to the same metric intended for men while facing additional challenges indicating a persistent glass ceiling.